2018
DOI: 10.1093/jhered/esy051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hidden Relatedness on Single-Step Genetic Evaluation in an Advanced Open-Pollinated Breeding Program

Abstract: Open-pollinated (OP) mating is frequently used in forest tree breeding due to the relative temporal and financial efficiency of the approach. The trade-off is the lower precision of the estimated genetic parameters. Pedigree/sib-ship reconstruction has been proven as a tool to correct and complete pedigree information and to improve the precision of genetic parameter estimates. Our study analyzed an advanced generation Eucalyptus population from an OP breeding program using single-step genetic evaluation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 60 publications
4
27
0
Order By: Relevance
“…In this study, we used single-step GBLUP (ssGBLUP), GBLUP and ABLUP models to estimate genetic parameters and to test the prediction accuracies of different traits in an E. pellita breeding population. Most of the previous studies in forest trees which used ssGBLUP have included only the additive effects in the model ( Ratcliffe et al 2017 ; Cappa et al 2017 , 2019 ; Klápšte et al 2018 ). In contrast, we used additive and dominance effects in ssGBLUP model to study the genetic parameters and to test prediction accuracies of different traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used single-step GBLUP (ssGBLUP), GBLUP and ABLUP models to estimate genetic parameters and to test the prediction accuracies of different traits in an E. pellita breeding population. Most of the previous studies in forest trees which used ssGBLUP have included only the additive effects in the model ( Ratcliffe et al 2017 ; Cappa et al 2017 , 2019 ; Klápšte et al 2018 ). In contrast, we used additive and dominance effects in ssGBLUP model to study the genetic parameters and to test prediction accuracies of different traits.…”
Section: Discussionmentioning
confidence: 99%
“…Application of markers in open-pollinated (OP) families is particularly useful as markers can uncover half-sib and full-sib relationships within the OP families ( El-Kassaby et al 2011 ). This will have a significant impact on the precision and accuracy of the estimated genetic parameters as demonstrated by a number of studies ( Bush and Thumma 2013 ; Gamal El-Dien et al 2016 , 2018 ; Müller et al 2017 ; Klápště et al 2017 ; Klápšte et al 2018 ). In traditional methods, all individuals of an OP family are treated as half-sibs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Forest tree progeny tests are typically large populations containing thousands of individuals, which has prevented full-scale genotyping [25]. Therefore, the combination of phenotype, pedigree and genomic information through a single-step evaluation approach [31] is the preferred strategy in forest tree breeding [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Through the H matrix, A is augmented by G and vice versa, enabling ssGBLUP to improve accuracy in the evaluation of breeding values for both genotyped and non-genotyped relatives. However, although ssGBLUP has several advantages to the multiple-step method as described above, the application of this method for plant breeding has been limited to several species, including rice ( Oryza sativa L.) [16,17], wheat ( Triticum aestivum L.) [18,19], maize ( Zea mays L.) [20], and those of forest trees [2124], and to the best of our knowledge, no previous studies of ssGBLUP have reported for fruit breeding. Accordingly, we applied ssGBLUP to a real dataset of fruit-quality traits obtained from an ongoing citrus breeding program.…”
Section: Introductionmentioning
confidence: 99%